2023
DOI: 10.3390/antibiotics12030425
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Pharmacogenomics to the Safe Use of Antimicrobials

Abstract: There has been widespread implementation of pharmacogenomic testing to inform drug prescribing in medical specialties such as oncology and cardiology. Progress in using pharmacogenomic tests when prescribing antimicrobials has been more limited, though a relatively large number of pharmacogenomic studies on aspects such as idiosyncratic adverse drug reactions have now been performed for this drug class. Currently, there are recommendations in place from either National Regulatory Agencies and/or specialist Pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Finally, genetics can condition the development of antibiotic-related adverse events, and the screening of patients with supposed or demonstrated specific genetic mutations may reduce the incidence of drug-related adverse events. Recent studies have shown that the mutation of genes encoding drug-metabolizing enzymes and transporters, genetic variants of some components of the immune system or mutations of mitochondrial genes are potentially associated with significant modifications of drug disposition [ 17 , 18 ]. This can lead to variations in drug clearance, with reduced drug efficacy or accumulation and an increase in the risk of adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, genetics can condition the development of antibiotic-related adverse events, and the screening of patients with supposed or demonstrated specific genetic mutations may reduce the incidence of drug-related adverse events. Recent studies have shown that the mutation of genes encoding drug-metabolizing enzymes and transporters, genetic variants of some components of the immune system or mutations of mitochondrial genes are potentially associated with significant modifications of drug disposition [ 17 , 18 ]. This can lead to variations in drug clearance, with reduced drug efficacy or accumulation and an increase in the risk of adverse events.…”
Section: Introductionmentioning
confidence: 99%